Romanticized Abusive Behavior by Media Narrative Analysis on Portrayal of Intimate Partner Violence Romanticism in Korean Drama - Priscila Asoka Kenasri; Lidwina Mutia Sadasri (Humaniora, 2021)
Intimate relationships are often depicted in terms of a  beautiful idealism, especially in the mass media. However, the evidence shows a vast number of women while in such a relationship have been subjected to physical, emotional, and/or sexual violence by their partner. Media plays an important part in shaping and reflecting social life, resulting in audience consumption of romanticized abusive behaviour. Its audiovisual content can perpetuate the point of view that some violence is normal  – even romantic. Such a point of view can be found in Korean dramas, which have been popular with its Indonesian audience for some  20 years and do not show any signs of a decline in popularity. This study aims to reveal a  narration of intimate partner violence portrayal as romance in the Korean drama The Heirs (2013). A qualitative method is used drawing on Propp's Seven Characters and Greimas' Actantial narrative analysis model. The research results show how The Heirs project romantic imagery masking abusive traits by establishing the male main character as a subject who forces a relationship without accepting rejection. Moreover, this study found the romanticization of abuse was amplified by depicting the female protagonist as an object expressing her objection to giving male characters the thrill of the chase. The findings in this research is consistent with the concept of romanticized media, particularly in portraying the romanticization of intimate partner violence.